A comparison of the learning effects between TGfU-SE and TGfU on learning motivation, sport enjoyment, responsibility, and game performance in physical education - Pan, Yi-Hsiang; Huang, Chen-Hui; Hsu, Wei-Ting (Frontiers in Psychology, 2023)
Background: Both the Sport Education (SE) model and Teaching Games for Understanding (TGfU) have been connected to the theory of situated learning, which is a game-centred curricular model. TGfU emphasizes that tactical awareness, decision making and skill execution. SE model provide a complete season during physical education (PE) lessons. Therefore, it is worthy to explore that integrate TGfU with SE model in PE course, whether the hybrid TGfU-SE model can achieve better learning effects for students than TGfU model along. Purpose: The purposes of the study were to compare the difference in learning effects between the TGfU-SE course and the TGfU course on students’ learning motivation, sport enjoyment, responsibility and game performance. Methods: This study used a quasi-experimental design to compare different learning effects between the experimental group (TGfU-SE) and the control group (TGfU). The participants lived in Taiwan, including 2 junior high school PE teachers and 4 PE classes with a total of 90 students (TGfU-SE group, n=46; TGfU group, n=44). Each teacher taught two PE classes, one with an experimental group and one with a control group. The research instruments were questionnaires and the Game Performance Assessment Instrument. Analysis of covariance (ANCOVA) was used to analyze the data. Results: The results of this study showed that the TGfU-SE program had more positive learning effects on students’ learning motivation, sport enjoyment, responsibility and game performance than the TGfU program. Conclusion: we concluded that the TGfU-SE program had a more positive influence on students’ learning performance than the TGfU program. It is suggested that, the hybrid TGfU-SE model could be implemented effectively in PE curriculum.